Learning from the Past: Meta-Analysis of Contextual Teaching-Learning of the Past Decade - Maximus Tamur; Valeria Suryani Kurnila; Marzuki Marzuki; Emilianus Jehadus; Sabina Ndiung; Jerito Pareira; Syaharuddin Syaharuddin (Universitas Muhammadiyah Mataram, 2021)
This meta-analysis was conducted to summarize the evidence linking the influence of Contextual Teaching-Learning (CTL) on students' mathematical abilities. The research data was obtained from the ERIC database, sage publishing, Scopus database, semantic scholarships, and google scholarships. The 26 studies that met the inclusion requirements were analyzed to obtain an estimate of effectiveness and examined the extent to which the effect of CTL was moderated by year of study, level of education, sample size, and publication source. The random-effect model is estimated, and data processing uses the Comprehensive Meta-Analysis (CMA) software. The results showed the overall effect size of the study was 0.88 (large effect). The moderator analysis results revealed that the implementation of CTL was moderated by the variables of education level and publication source. On the other hand, the studies' heterogeneity reflects that there are still other moderating variables associated with the effectiveness of CTL. The study's limitations and implications are discussed as the basic idea for the implementation of further research.